Inhibition and potential treatment of colorectal cancer by natural compounds via various signaling pathways - Wang, Mingchuan; Liu, Xianjun; Chen, Tong; Cheng, Xianbin; Xiao, Huijie; Meng, Xianglong; Jiang, Yang (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is a common type of malignant digestive tract tumor with a high incidence rate worldwide. Currently, the clinical treatment of CRC predominantly include surgical resection, postoperative chemotherapy, and radiotherapy. However, these treatments contain severe limitations such as drug side effects, the risk of recurrence and drug resistance. Some natural compounds found in plants, fungi, marine animals, and bacteria have been shown to inhibit the occurrence and development of CRC. Although the explicit molecular mechanisms underlying the therapeutic effects of these compounds on CRC are not clear, classical signaling transduction pathways such as NF-kB and Wnt/β-catenin are extensively regulated. In this review, we have summarized the specific mechanisms regulating the inhibition and development of CRC by various types of natural compounds through nine signaling pathways, and explored the potential therapeutic values of these natural compounds in the clinical treatment of CRC.